Photocatalytic Activity and Optical Properties of Blue Persistent Phosphors under UV and Solar Irradiation - C. R. García; L. A. Diaz-Torres; J. Oliva; M. T. Romero; P. Salas (International Journal of Photoenergy)
Blue phosphorescent strontium aluminosilicate powders were prepared by combustion synthesis route and a postannealing treatments at different temperatures. X-ray diffraction analysis showed that phosphors are composed of two main hexagonal phases: SrAl2O4 and Sr3Al32O51. The morphology of the phosphors changed from micrograins (1000°C) to a mixture of bars and hexagons (1200°C) and finally to only hexagons (1300°C) as the annealing temperature is increased. Photoluminescence spectra showed a strong blue-green phosphorescent emission centered at λem=455 nm, which is associated with 4f65d1→4f6  (8S7/2) transition of the Eu2+. The sample annealed at 1200°C presents the highest luminance value (40 Cd/m2) with CIE coordinates (0.1589, 0.1972). Also, the photocatalytic degradation of methylene blue (MB) under UV light (at 365 nm) was monitored. Samples annealed at 1000°C and 1300°C presented the highest percentage of degradation (32% and 38.5%, resp.) after 360 min. In the case of photocatalytic activity under solar irradiation, the samples annealed at 1000°C, 1150°C, and 1200°C produced total degradation of MB after only 300 min. Hence, the results obtained with solar photocatalysis suggest that our powders could be useful for water cleaning in water treatment plants.